Building the Foundation for Creativity and Collaboration: Knowledge Sharing Learning Models - Mustaqim, Ilmawan; Setyosari, Punaji; Kamdi, Waras; Ulfa, Saida (Jurnal Cakrawala Pendidikan, 2024)
The integration of creativity, critical thinking, collaboration, and communication skills into 21st-century learning represents a pivotal goal in education, particularly within the realms of engineering. Despite this ambition, the actualization of creativity and collaborative capabilities among engineering students remains a significant challenge, primarily due to prevalent individualistic attitudes and apprehensions towards error in idea sharing. This study introduces and evaluates a Knowledge Sharing (KS) learning model aimed at overcoming these barriers, thereby facilitating enhanced creativity and collaboration. Employing the Akker learning stages, this model was implemented in an engineering education setting, yielding encouraging outcomes: students demonstrated increased motivation for interdisciplinary learning, acquired novel knowledge beyond their traditional curricula, and developed practical designs and tools responsive to community needs. The methodology section details the iterative process of model development, encompassing identification, design and preparation, implementation, replication, and dissemination phases, followed by a thorough validation process. Results indicate a positive impact on students' creative competencies and collaborative skills, underscoring the model's efficacy in fostering essential 21st-century skills.